2012
DOI: 10.1016/j.jtcvs.2012.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the indications for the David V aortic root replacement: Early results

Abstract: In selected patients possessing appropriate aortic cusp anatomy, the David V can be safely and effectively performed for the expanded indications of aortic dissection, severe AI, and reoperative cardiac surgery with low operative risk. Valve function has remained excellent in the short term, providing evidence of durability and a low rate of valve-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 26 publications
(32 reference statements)
2
32
0
Order By: Relevance
“…In our own institutional experience, it has been previously reported that VSRR operations could be performed with acceptable operative mortality in clinical scenarios that have been typically associated with higher operative risk, including significant aortic insufficiency, reoperative cardiac surgery, and acute type A dissection [11,12]. When applied using appropriate anatomic criteria, valve durability and freedom from moderate aortic insufficiency have been acceptable at midterm follow-up, exceeding 90% [11,12].…”
Section: Commentmentioning
confidence: 84%
See 3 more Smart Citations
“…In our own institutional experience, it has been previously reported that VSRR operations could be performed with acceptable operative mortality in clinical scenarios that have been typically associated with higher operative risk, including significant aortic insufficiency, reoperative cardiac surgery, and acute type A dissection [11,12]. When applied using appropriate anatomic criteria, valve durability and freedom from moderate aortic insufficiency have been acceptable at midterm follow-up, exceeding 90% [11,12].…”
Section: Commentmentioning
confidence: 84%
“…The Emory technique of the David V VSRR and arch replacement has been described previously [11,12]. Patients undergoing isolated aortic root replacement received central aortic and right atrial cannulation.…”
Section: Surgical Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…The Emory technique of the David V and aortic arch replacement has been described previously [11,12]. Transcutaneous cerebral oximetry (INVOS 3100-SD, Troy MI) and continuous electroencephalographic monitoring were performed on every patient.…”
Section: Surgical Techniquementioning
confidence: 99%